Frequently reported blood biomarkers in sarcopenia clinical trials: a systematic review and meta-analysis - Calluy, Emma; Malrechauffé, Yveline; Boretti, Emma; Van Heden, Sophie; Sanchez-Rodriguez, Dolores; Chan, Yoke Mun; Cavalier, Etienne; Ladang, Aurélie; Reginster, Jean Yves; Douxfils, Jonathan; Beaudart, Charlotte (John Wiley and Sons, 2026)
This systematic review and meta-analysis aims to identify the most frequently reported blood-based biomarkers (BBMs) in randomised controlled trials (RCTs) addressing sarcopenia management, and to perform a preliminary evaluation of the effects of sarcopenia-specific interventions on BBMs concentrations. Medline, Embase and CENTRAL databases were searched to retrieve RCTs published until March 2024 (PROSPERO: CRD42024603238) on older participants with sarcopenia. Eligible studies applied a consensus definition of sarcopenia and reported BBM values before and after intervention. Meta-analyses were performed for BBMs reported in a minimum of 2 RCTs using a random effects model with a standardised mean difference (SMD) and a 95% confidence interval. Among 58 RCTs on sarcopenia management, only 21 (36.2%) assessed BBMs and none involved pharmacological interventions. Altogether, 47 distinct BBMs were identified. The most frequently reported were C-reactive protein, interleukin 6, tumour necrosis factor α, Insulin-like Growth Factor 1 (IGF-1). Muscle-specific BBM, follistatin, growth differentiation factor 8 and 15 were assessed in only 2 RCTs. Among non-muscle-specific BBMs, IGF-1 was significantly impacted by the studied interventions (SMD = 0.46, CI = [0.04; 0.88]). However, this change was not significant when analyses were restricted to RCTs reporting significant improvement in key sarcopenia measures. Despite substantial heterogeneity, few BBMs assessed in sarcopenia RCTs were muscle-specific and limited biomarkers responded to interventions. There is an urgent need to adopt recommendations regarding muscle-specific BBMs to be assessed in sarcopenia RCTs. Developing a standardised Core Outcome Set for sarcopenia intervention studies would enhance the standardisation of sarcopenia RCTs and ultimately improve disease management.